Disrupting the vicious cycle of malnutrition and enteropathy: advancing strategies to improve child physical and neurocognitive outcomes - M. Khalid Ijaz; Raymond W. Nims; Joseph R. Rubino; Bushra S. F. Hasan; Maryum K. Ijaz; Frank Y. Xu; Charles P. Gerba (Frontiers in Public Health, 2026)
Background Recognition of the synergistic cycle of malnutrition, immune dysfunction, and recurrent enteric infection in children and its role in linear growth stunting and impaired cognitive development (the “stunting syndrome”), dates back to the 1960s. Early hypotheses emphasized reduced intestinal absorption associated with diarrhea as the primary enteropathy driving malnutrition and developmental deficits. However, recent evidence indicates that a subclinical condition termed environmental enteropathy (EE), or environmental enteric dysfunction (EED), may be a more critical contributor. Mitigating the adverse impacts of EE/EED requires a holistic, integrated approach that combines improved nutrition, water, sanitation, and hygiene (WASH), appropriate vaccination, and targeted non-pharmaceutical hygiene interventions designed to prevent recurrent enteric infections. These interventions aim to reduce pathogen exposure in infants’ immediate environments, a prerequisite for achieving sustained physical and neurocognitive development and, ultimately, economic progress in low- and middle-income countries (LMICs). Objective This Hypothesis and Theory article synthesizes current understanding of EE/EED as a proximate driver of chronic childhood malnutrition and its major sequelae: stunting, impaired neurocognitive development, immune dysfunction (including poor pediatric vaccine response), and nutrient malabsorption. We hypothesize the necessity of reducing enteric infection occurrence as a cornerstone for breaking the malnutrition–infection cycle and propose that non-pharmaceutical interventions targeting pathogen exposure in household and infant play environments are essential. In addition to pathogen exposure, we examine other determinants of malnutrition, including microbiome dysbiosis and epigenetic alterations as possible targets for therapeutic interventions intended to mitigate negative outcomes on health and nutrition. Methods We reviewed literature addressing malnutrition, immune impacts, enteric infections, EE, growth stunting, cognitive impairment, epigenetic alterations, and mitigation strategies including WASH, baby WASH, hand and surface hygiene, and vaccination, using databases such as PubMed, Embase, and Google Scholar. Results The synergistic malnutrition and infection cycle underlying the stunting syndrome comprises multiple interdependent components: chronic malnutrition, immune dysfunction, recurrent pathogen assault, microbiome dysbiosis, and EE/EED. Previous interventions have largely failed, likely because they targeted isolated components rather than the entire cycle. Here, we describe this cycle, its interactions, and prior attempts at disruption. We advocate for a novel, integrated approach, termed baby WASH or environmental hygiene, focused on creating hygienically clean environments where infants live and play, thereby reducing exposure to enteric pathogens. We also explore the link between malnutrition, EE/EED, and epigenetic reprogramming, as a contributor to health risks. Importantly, malnutrition is linked to epigenetic reprogramming, which contributes to neurocognitive impairment. We hypothesize that by combining baby WASH strategies with emerging pharmaceutical interventions addressing epigenetic and nutritional deficits, and associated socioeconomic and political factors, a comprehensive maternal–child health framework may be established to interrupt this vicious cycle. Conclusion Preventing recurrent pathogen exposure during both prenatal and postnatal periods is hypothesized to be essential to interrupting the malnutrition and infection cycle and reducing stunting. Interventions must address infants’ immediate living, feeding, and educational environments, as well as maternal environments during gestation. Early-life nutritional deficiencies may influence epigenetic programming, with developmental consequences. Breaking this cycle remains an unmet global health priority, warranting urgent international attention due to the human and economic tolls in resource-limited settings LMICs.